The name to be used for the most invasive species of Kalanchoe globally finally resolved: nomenclature and taxonomy of the Malagasy Kalanchoe delagoensis (Crassulaceae subfam. Cotyledonoideae) - Smith, Gideon F. (Phytotaxa, 2024)
For the past nearly 190 years, uncertainty has surrounded the correct name that has to be used for the species of Kalanchoe (Crassulaceae subfam. Cotyledonoideae) most commonly recorded as weedy, naturalised, or invasive in, especially, mild-climate parts of the world well away from its natural habitat in Madagascar. Two names, K. delagoensis (published in 1837 by Ecklon & Zeyher) and K. tubiflora (published in 1912 by Raymond-Hamet), were, up to now, widely used for this species. In its protologue, the name K. delagoensis was furnished with a very cryptic, three-word descriptive statement that has resulted in this name not having been adopted by many authors on Kalanchoe because the name was considered as not having been validly published. For this reason and to resolve this matter, a request for a binding decision on whether the name K. delagoensis was validly published (in 1837 by Ecklon and Zeyher; the name K. tubiflora was undoubtedly validly published in 1912, based on Bryophyllum tubiflorum) was submitted for consideration by the Nomenclature Committee for Vascular Plants (NCVP). The NCVP considered the matter and recommended that K. delagoensis was indeed validly published by Ecklon & Zeyher, which makes the name K. tubiflora, which was published 75 years later by Raymond-Hamet, nomenclaturally superfluous. The nomenclature associated with the name K. delagoensis is reviewed; its homo- and heterotypic synonymy is provided; the name K. verticillata, a heterotypic synonym of K. delagoensis, is lectotypified; and an amplified description and illustrations are provided of the species, as well as illustrations of the invasive K. ×houghtonii, of which it is one parent.